Shear resistance of oil palm shell concrete beams with and without shear reinforcement - Chin, Mei Yun (2014)
In recent years, the use of Oil Palm kernel Shell (OPS) aggregate as coarse aggregate in concrete has received increasing attention due to its environmental and economic benefits. To date, considerable amount of research have been carried out to aid the understanding of its concrete mixture designs and its material properties, but, only limited amount of works have been carried out to aid the current understanding with respect to its shear resistance.